2015
DOI: 10.4236/psych.2015.64044
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Cognitive Therapy: Primary Care Patients’ Experiences of Outcomes in Everyday Life and Relapse Prevention

Abstract: The concept of mindfulness has attracted a growing body of research within behavioural medicine over the last decade. Mindfulness-based cognitive therapy (MBCT) has been developed to prevent relapse among people who suffer recurrent depression. Studies show impressive results, with a decrease in the risk of relapse of up to 50%. However, primary care patients' own experiences and MBCT's effectiveness as a relapse program and aid to their ability to deal with everyday life remain relatively unexplored. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Overall, our findings fit with other qualitative investigations of MBCT (Cairns & Murray, 2015;Chesin et al, 2018;Lilja et al, 2015;Malpass et al, 2012;Murphy & Lahtinen, 2015;Tickell, Ball, et al, 2020;Tickell, Byng, et al, 2020;Williams et al, 2018;Wyatt, Harper, & Weatherhead, 2014). Our findings fit most similarly with the 'relating mindfully' model proposed by Bihari and Mullan (2014).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our findings fit with other qualitative investigations of MBCT (Cairns & Murray, 2015;Chesin et al, 2018;Lilja et al, 2015;Malpass et al, 2012;Murphy & Lahtinen, 2015;Tickell, Ball, et al, 2020;Tickell, Byng, et al, 2020;Williams et al, 2018;Wyatt, Harper, & Weatherhead, 2014). Our findings fit most similarly with the 'relating mindfully' model proposed by Bihari and Mullan (2014).…”
Section: Discussionsupporting
confidence: 90%
“…Clinical and applied researchers often draw a distinction between cognitive and behavioral orientations when implementing interventions (see Young et al, ). Cognitive approaches to therapy, which include mindfulness‐based cognitive therapy, emotion‐focused therapy, and compassion‐focused therapy, have been shown to reduce depression and anxiety as well as improve recovery from psychosis (Lilja, Broberg, Norlander, & Broberg, ; Mason & Hargreaves, ; Meeten, Whiting, & Williams, ).…”
Section: Personality Change Through Adulthoodmentioning
confidence: 99%
“…For instance, Lilja et al () observed that individuals who suffered from depression not only saw a decrease in symptoms after a 2‐week mindfulness meditation intervention, but also reported continued use of mindfulness during a 12‐month follow‐up. More active, behavioral approaches to personal change (e.g., facing one's social phobia or lack of self‐esteem by going to a party or regularly asserting oneself), in contrast, have been found to reduce fear arousal, recurrence in major depression, and symptomatic exacerbation of schizophrenia (Bandura, Adams, & Beyer, ; Dobson et al, ; Glynn et al, ; Pagoto et al, ).…”
Section: Personality Change Through Adulthoodmentioning
confidence: 99%
“…A report on Evidence-Based Practice in psychology (American Psychological Association, 2006) emphasized the importance of an integration of science and practice where one of the points was that "qualitative research can be used to describe the subjective, lived experiences of people, including participants in psychotherapy" (p. 274), which may lead to the identification of parameters that can improve treatment outcomes. It is in line with the qualitative premise that it is the patient himself/herself who is the best judge of his/her process and experience (Lilja, Broberg, Norlander, & Broberg, 2015). Malterud (2001) proposes not to consider quantitative and qualitative strategies as incompatible, but should be seen as complementary to each other because the underlying principles have much in common.…”
Section: Abrahamsson Et Almentioning
confidence: 79%